Preconception Health Behavior Patterns and Their Relationship With Women’s Reproductive Health in The Cibatu District, Purwakarta - Mony, Bosyahamu (Jurnal Indonesia Sosial Sains, 2025)
Background: Good preconception health behaviors are an important step in preparing for a healthy pregnancy and optimizing a woman's reproductive health. However, many women of childbearing age have not implemented adequate preconception behavior patterns. Objective: To find out the pattern of preconception health behavior of women of childbearing age and the relationship between these behaviors and reproductive health status in Cibatu District, Purwakarta. Methods: Quantitative research with cross-sectional design. A sample of 100 women of childbearing age (20–35 years) was selected using purposive sampling techniques. Data were collected through questionnaires of preconception behaviors (nutritional intake, physical activity, health checks, and lifestyle) as well as reproductive health records. Data analysis used Pearson correlation test and logistic regression. Results: Most respondents (60%) had moderate, 25% good, and 15% less preconception behavior. There was a significant positive association between preconception health behaviors and reproductive health status (p = 0.002, r = 0.421). Conclusion: Good preconception health behavior patterns are closely related to women's reproductive health.